The Reconstruction of Khilafah : Study on The New KMA183 Curriculum for Madrasah - M, Zaki (Politea : Jurnal Politik Islam, 2020)
This paper discusses the concept of caliphate which is one of the substances of Islamic education learning in Islamic School, and the development of its paradigm toward a form of contextualization of the vision, mission and strategy of national education development. This study focuses on several changes in the content of the Islamic Education Studies and Arabic Studies which included in KMA 183 in 2019, the lesson of caliphate has been moved from the Fiqh subject to Islamic Cultural History. This study uses an interpretive descriptive approach, which is a method and approach in the study of beliefs, ideas and discourses that are developing around the KMA 183 policy. This study produces a conclusion about policy-making from various aspects, one of them is an effort to contextualize the Islamic Education Studies. and Arabic Studies in order to be “in tuned” with the vision and mission of the national education strategy. The author concludes that the reconstruction of khilafah’s term from the context of Islamic law to Islamic civilization actually builds a new wave of Islamic political treasures which not only touch the cognitive area, but also become a reflection as well as actualization in the dimensions of social life.